PENERAPAN MODEL GROUP INVESTIGATION UNTUK MENINGKATKAN KREATIVITAS GERAK TARI SISWA SMAN 2 PONTIANAK - Pratiwi, Agus; Istiandini, Winda; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this study is class XI MIA 2 students of SMA Negeri 2 Pontianak which had no experience in dancing, lack of confidence in delivering the idea of movement, and the students? power of imagination was low to find dance movements. In class XI MIA 2, there were only 2 of 40 students who participated in the studio. Besides that, art and culture teacher still used the conventional technique, namely lecture technique which ensued one-way teaching and learning process. In this case, the students? position is absolutely passive that made them became the party receiver. Whereas in learning dance art demands the students to be active, creative, and innovative. This research is an action research by using descriptive research technique and qualitative approach. After the teaching and learning process was implemented from cycle 1 to cycle 2, the stage of the students? dance creativity increased from 1,82 to 3,77 and the result of students? dance movements also increased from 2,26 to 3,99. The conclusion of this research is the students? creativity in dance movement material can be improved by using Group Investigation learning model. Keywords: Group Investigation Learning Model, Students? Creativity, and Dance Movements